Perceptions of fruit and vegetable dietary guidelines among Australian young adults - Kothe, E.; Mullan, Barbara (Wiley-Blackwell Publishing Asia, 2011)
Aim: Regular consumption of fruit and vegetables has been associated with a decreased risk of a number of chronic diseases. An appropriate level of knowledge is important to successfully adhere to the dietary guidelines for eating fruit and vegetables. However, there is little research about the level of knowledge that young adults have about fruit and vegetable consumption. The current study aimed to investigate the recall and understanding of Australian dietary guidelines, food product and serving size knowledge in a population of young adults. Methods: One hundred and six undergraduate students completed online questionnaires regarding (1) knowledge of dietary recommendations; (2) knowledge of serving size information; and (3) foods that could be included as part of fruit and vegetable intake. Results: The results showed that the sample had significant knowledge gaps in all three areas. Approximately half (54%) of participants correctly reported the recommended daily intake of fruit and vegetables, the majority were not able to correctly report serving sizes (correct responses were 30–61%) and were not able to identify all ingredients from a recipe that counted towards fruit and vegetable intake. Conclusions: Past interventions have not tended to focus on the fruit and vegetable knowledge, or behaviours, of Australian young adults. On the basis of findings from this study, it appears that more work is needed to develop messages to effectively target this important group.